Pelatihan Penyelenggaraan Event sebagai Promosi Destinasi Desa Wisata Pantai Minang Rua Lampung Selatan - Damara Saputra Siregar; Ani Novita Sari; Gita Hilmi Prakoso; Helidatasa Utami; Desmala Sari; Nelly Suryani; Tina Nurzachra Latifah Rizky Liana; Riyan Maruli (Lembaga Pengembangan Kinerja Dosen, 2025)
Minang Rua Beach in South Lampung possesses significant tourism potential that has not been optimally utilized, primarily due to the lack of creative promotional events and limited community skills in event management. This community service aimed to enhance the capacity of the local Tourism Awareness Group (Pokdarwis) and youth in designing, managing, and promoting tourism events effectively. The method employed was a participatory training approach that included lectures, discussions, and hands-on practice covering creative event design, logistics management, budgeting (RAB), and digital promotion strategies. The training activities were met with high enthusiasm and active participation from the community members. The participants gained new, practical knowledge and skills in event planning and promotion, as demonstrated by their active engagement during interactive sessions and simulations. The improved capacity of the local community is expected to foster the independent and sustainable organization of creative events, thereby enhancing the destination's attractiveness and increasing tourist visits. Event Training, Tourism Promotion, Community Empowerment, Tourism Village, Minang Rua Beach.